Optimalisasi Dana Peningkatan Kesiapsiagaan Bahaya Kebakaran dan Bencana Dalam Perspektif Disaster Risk Management - Muhammad Febriansyah Rohimat; Abdal Abdal; Rahayu Kusumadewi (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2022)
The establishment of disaster preparedness in the community is a very important thing to be done by the government. This is because Indonesia is located in the ring of fire belt areas which causes a variety of potential disasters. In dealing with this, Bandung city government through the Bandung City Fire and Disaster Management Office established a program in order to improve preparedness. Therefore, the government needs to optimize the available budget in order to achieve this goal. The research objective to be achieved in this paper is to analyze how the optimization of funds for the Fire and Disaster Preparedness and Prevention Program from the perspective of disaster risk management in the Bandung City Fire and Disaster Management Office. This research is a descriptive research utilizing qualitive method. Data collection was conducted using structured interviews, literature reviews, and unstructured observations in research locations. The result of this research is the formation of disaster preparedness in the community has not been fully optimized. This is due to the non-fulfillment of existing parameters in disaster risk management such as knowledge about disasters, emergency planning, and warning systems. Keyword: Disaster Preparedness, Disaster Risk Management, Fund Optimazation